Prevalence of work-related stress and its associated factors among bank workers in Gondar city, Northwest Ethiopia: A multi-center cross-sectional study - Enyew Getaneh Mekonen; Belayneh Shetie Workneh; Mohammed Seid Ali; Beletech Fentie Abegaz; Mulugeta Wassie Alamirew; Agazhe Aemro Terefe (Elsevier, 2022)
Introduction: Work-related stress is a cognitive, emotional, behavioral, and psychological response to aversive and apprehensive features of work, work environments, and work administration. It is a health and safety risk among employees working in different sectors and organizations, including the banking sector. It decreases workers' productivity in the banking sector as workers' performance can be deferred by high levels of stress faced in the work atmosphere. Therefore, this study was conducted to assess the prevalence of work-related stress and its associated factors among bank employees in Gondar city, Northwest Ethiopia. Methods: The study was conducted from 20th October to 10th November 2020 at banks in Gondar city using an institution-based cross-sectional study design. A simple random sampling technique was used to select 296 participants. Data were collected using a structured pretested self-administered questionnaire. Epi-info version 7 and SPSS version 21 were used for data entry and analysis respectively and presented using frequencies, percentages, tables, and graphs. Bivariable and multivariable analyses were carried out using a binary logistic regression model. Statistical significance was declared at a p-value < 0.05. Result: The prevalence of work-related stress among bank employees was 21.1% with a 95% CI (16.5%, 25.3%). Being male [AOR: 0.43; 95% CI (0.20, 0.94)], alcohol use [AOR: 3.04; 95% CI (1.59, 5.80)], and having a history of chronic disease [AOR: 3.36; 95% CI (1.82, 6.22)] increase the risk of developing work-related stress. Conclusion: More than one-fifth of the bank workers in Gondar city had work-related stress. Sex, having history of chronic diseases, and alcohol use were significantly associated with work related stress.